Metode Pembelajaran Bertahap Perspektif al-Ghazali dan Implementasinya di TPQ al-Huda Dukuhturi Tegal - Moh. Sobirin (Fakultas Ilmu Tarbiyah dan Keguruan, Institut Agama Islam Bakti Negara Tegal, 2026)
This study was motivated by the low level of Qur’anic literacy among Indonesian Muslims and the importance of implementing learning methods that are appropriate to students’ developmental stages in Qur’anic education. The study aims to describe al-Ghazali’s concept of gradual learning methods and their implementation at TPQ al-Huda Dukuhturi Tegal. This research employed a qualitative approach with a field research design. Data were collected through participatory observation, in-depth interviews, and documentation involving foundation administrators, TPQ principals, teachers, students, and alumni of TPQ al-Huda. The findings reveal that al-Ghazali’s gradual learning method is implemented through sequential material delivery from simple to complex concepts, from concrete to abstract understanding, and adjusted to students’ abilities and psychological development. The implementation is reflected in the use of classical-individual learning systems, staged Tilawati learning, memorization habituation, gradual reading exercises, and continuous evaluation. In addition, teachers play an active role in adapting instructional methods to the characteristics of learners, making the learning process more effective and easier to understand. The study concludes that the implementation of al-Ghazali’s gradual learning method at TPQ al-Huda successfully improves students’ ability to read the Qur’an fluently, correctly, and progressively according to their developmental stages.